Hubungan Jenis Kontrasepsi dengan Status Gizi dan Asupan Makronutrien pada Wanita Usia Subur (WUS) di Kecamatan Tebet: Hubungan Jenis Kontrasepsi dengan Status Gizi dan Asupan Makronutrien pada Wanita Usia Subur di Kecamatan Tebet - Arfini, Lusiani; Octaria, Yessi Crosita; Fauziyah, Aimmatul; Sufyan, Dian Luthfiana (Amerta Nutrition, 2024)
Background: Female obesity prevalence was higher than male in 2018 at 44.4% and 26.6%, respectively, according to Badan Pusat Statistik (BPS). There is conflicting evidence on the effect of hormonal contraception on weight gain. While in Indonesia, hormonal contraception has been the most popular method. Objectives: Examining the association between hormonal contraception usage, macronutrient consumption, and nutritional status. Methods: This cross-sectional study involves 106 non-pregnant women aged 20-45 recruited using consecutive sampling methods. Respondents were grouped into hormonal and non-hormonal contraceptive users. Data analysis utilized chi-square, Fischer exact and multiple linear regression. Results: More than half (59.5%) used hormonal contraception, while 40.5% used non-hormonal contraceptives. We found no significant correlation between hormonal contraception and Body Mass Index (BMI) (p-value=0.081), waist circumference (p-value=0.789), and macronutrient intake (p-value of energy=0.0675; protein=0.758; fat=0.156; carbohydrate=0.23). There was no significant relationship between the duration of contraceptive usage and BMI (p-value=0.163 and 0.248) or waist circumference (p-value=0.282 and 0.066) for either users or nonusers. Linear regression models showed that only fat and carbohydrate intake significantly contribute to waist circumference (The adjusted R2 of the model was 0.244, F 12.3, Sig.<0.001) and BMI (The adjusted R2 of the model was 0.206, F 7.8, Sig.<0.001). Conclusions: There was a relationship between BMI, body fat percentage, junk food consumption pattern (type, frequency, amount of intake and fat), energy intake, fat intake, emotional overeating, diet attitude, and oral control of the abdominal circle. There was no significant relationship between fiber intake and abdominal circumference.